Zenon z Elei – doksografia i fragmenty - Wesoły, Marian (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2013)
After a very general exegetical introduction, we put forward a new arrangement and translation of the major testimonies on Zeno of Elea. The few passages that are generally regarded as fragmenta verbatim are also cited in the original. The source material is presented in a reconstructive order that is somewhat different from the previous editions of Zeno. Our aim is to capture the specific problematic context of the ancient authors who refer and question Zeno’s arguments, without isolating and break up theses texts. The particular passages have been provided with thematic headings.
Zeno of Elea – doxography and fragments
The meager second-hand reports on the life of Zeno of Elea and his book with the famous paradoxes is rather seen as testimonies of his reception or criticism, coming chiefly from Plato, Aristotle, Eudemus and Simplicius. The last author in his extensive commentary to Aristotle’s Physics has preserved several citations from Zeno’s work that still are subject of various interpretations and controversies. While Zeno’s paradoxes are one the most often cited of themes in all Pre-Socratics, there is still no recent and more exhaustive edition of ancient testimonies on this challenging thinker. Most doubts and controversies are due to the deficiency and divergence of the source data, the difficulties of reading various passages in the texts that tend to be frequently complicated by the scholars. In his Parmenides, Plato mentions Zeno’s arguments against plurality rather selectively and one-sidedly, citing only one of them and totally disregarding other paradoxes. On the other hand, Aristotle in his Physics, discusses somewhat differently and more extensively the context of Zeno’s aporias concerning the one – many, infinite divisibility, motion, place and sound. The same issue is taken up by Simplicius in his commentary. It remains highly debatable whether Zeno, in opposition to Parmenides, formulated also his arguments against the one as an indivisible point, which Aristotle and Eudemus seem to suggest. That is why Zeno was called double-tongued, since he was regarded as the discoverer of dialectic understood as a method of constructing argument on both sides, i.e., posing only aporetic issues without trying to resolve them. According to Aristotle, Zeno’s arguments were still an object of heated discussions. He viewed Zeno’s aporias as paralogisms, i.e., arguments that presuppose fallacious premises and conclusions, suggesting also its own solutions. Nevertheless, in modern times, though in quite different problematic context, Zeno’s paradoxes attracted most eminent philosophers and mathematicians, who constructed highly sophisticated theoretical models for the purpose of analyzing and solving the problems posed by Zeno. While theoretically Zeno of Elea still remains an important point of reference here, these solutions significantly exceed the historical reading of his arguments.
Keywords: Zeno of Elea; Zeno’s dialectic; infinite divisibility, motion, place, and sound; Plato’s and Aristotle’s account of his arguments against the one – many